VD_FINDINFO Jug / 2020 / 160 vom 3. Dezember 2019 - VD Tribunal cantonal (2019)
PRÉSOMPTION D'INNOCENCE, VOIES DE FAIT, MENACEDROIT PÉNAL, USAGE ABUSIF, VIOLATION DE DOMICILE | 126 CP, 179septies CP, 180 al. 2 let. a CP, 186 CP, 10 CPP (CH)